2002
DOI: 10.2135/cropsci2002.1688
|View full text |Cite
|
Sign up to set email alerts
|

Disomic Inheritance, Suppressed Recombination, and Allelic Interactions Govern Apospory in Buffelgrass as Revealed by Genome Mapping

Abstract: lecular markers within mapping populations (Wendel and Parks, 1984;Torres et al., 1985; Molecular tools have not identified the gene(s) governing apomixis Paterson et al., 1988Paterson et al., , 1991Saito et al., 1991; Lyt-nor have they been used to successfully transfer the trait to important, sexually reproducing food crops. Several molecular studies addressing tle, 1991;Schon et al., 1991; Zivy et al., 1992; Causse et apomixis in grasses have used interspecific and intergeneric hybrids. al., 1994; Chittend… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
33
0

Year Published

2004
2004
2017
2017

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 41 publications
(35 citation statements)
references
References 53 publications
2
33
0
Order By: Relevance
“…This no doubt results from the apomictic reproductive mode of C. ciliaris that leads to the formation of seeds genetically identical to the mother plant (Ozias-Akins et al 2003;Akiyama et al 2005). As stated above, apomixis is a heritable trait (Grimanelli et al 2001;Jessup et al 2002;Curtis and Grossniklaus 2007;Ozias-Akins and Van Dik 2007;Yadav et al 2012), but is rarely obligatory, and such is the case for C. ciliaris. In mixed breeding systems (sexual and apomictic), the genetic factors controlling apomixis can be potentially transferred from an apomictic individual to the offspring of a sexual plant via pollen.…”
Section: Intra-specific Phenotypic Variationmentioning
confidence: 99%
See 1 more Smart Citation
“…This no doubt results from the apomictic reproductive mode of C. ciliaris that leads to the formation of seeds genetically identical to the mother plant (Ozias-Akins et al 2003;Akiyama et al 2005). As stated above, apomixis is a heritable trait (Grimanelli et al 2001;Jessup et al 2002;Curtis and Grossniklaus 2007;Ozias-Akins and Van Dik 2007;Yadav et al 2012), but is rarely obligatory, and such is the case for C. ciliaris. In mixed breeding systems (sexual and apomictic), the genetic factors controlling apomixis can be potentially transferred from an apomictic individual to the offspring of a sexual plant via pollen.…”
Section: Intra-specific Phenotypic Variationmentioning
confidence: 99%
“…In C. ciliaris, apospory inherits as a dominant trait under genetic control of a single locus and transmits with an aposporyspecific genomic region (ASGR) located on a single chromosome (Roche et al 1999;Jessup et al 2002;Ozias-Akins and Van Dik 2007). Cytogenetic investigations of tetraploid C. ciliaris have demonstrated that the ASGR is located near the centromere in a genomic region that is hemizygous and heterochromatic (condensed part of chromatin genetically inactive) (Goel et al 2003(Goel et al , 2006Ozias-Akins et al 2003;Akiyama et al 2005).…”
Section: Facultative Nature Of Apomixis In Cenchrus Ciliarismentioning
confidence: 99%
“…Since the AFLP map of P. squamulatum provided only one closely recombining marker, we chose a second recombining marker from buffelgrass ( Jessup et al 2002), linked with the ASGR at a distance of 10.7 cM, to investigate by using BAC-FISH. The probe used to generate this marker in buffelgrass was from a sorghum cDNA library (HHU27, GenBank nos.…”
Section: Singleton C701mentioning
confidence: 99%
“…Our survey of 16 Pennisetum and two Cenchrus species has identified one that shows the presence of two ASGR-carrier chromosomes (Y. Akiyama, S. Goel, W. W. Hanna, P. Ozias-Akins, unpublished results). Jessup et al (2002) reported recombination of numerous markers and apospory in C. ciliaris even though some markers previously had been shown to be tightly linked with apospory (UGT197 and Q8) in both P. squamulatum (Ozias-Akins et al 1998) and a different population of C. ciliaris (Roche et al 1999). We investigated one of their recombining markers (HHU27) by isolating a BAC clone from C. ciliaris (C1000) that contained sequences from this marker.…”
Section: Recombination In the Asgr-carrier Chromosomementioning
confidence: 99%
See 1 more Smart Citation